Unique genetic background and outcome of non‐Caucasian Japanese probands with arrhythmogenic right ventricular dysplasia/cardiomyopathy. Issue 6 (13th August 2017) - Wada, Yuko; Ohno, Seiko; Aiba, Takeshi; Horie, Minoru
Abstract: Background: Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is an inherited cardiomyopathy mainly caused by desmosomal gene mutation. More than half of Caucasian probands have desmosomal mutations, which lead to earlier onset of ventricular arrhythmias. Among non‐Caucasians, the genetic background of ARVD/C probands and its prognostic impact remain unclear. Methods and Results: We genotyped 99 unrelated Japanese ARVD/C probands for plakophilin 2 ( PKP2 ), desmoglein 2 ( DSG2 ), desmoplakin ( DSP ), and desmocollin 2 ( DSC2 ) between 2005 and 2014. Seventy‐five probands who fulfilled "definite" category according to the 2010 Task Force Criteria (TFC) were enrolled and followed up for 6.4 years. Sixty‐four percent of probands had desmosomal mutations; DSG2 was predominant (48% of mutations) followed by PKP2 (38%). DSG2 mutations were almost missense, whereas over 90% of PKP2 mutations were truncating mutations. Lethal ventricular arrhythmias (VAs, sustained ventricular tachycardia/fibrillation) occurred in 57% of probands as the first manifestation and 71% at the end of follow‐up. Five died during follow‐up. Truncating mutation carriers exhibited earlier lethal VAs onset compared to missense mutation carriers or mutation negatives (age at onset 35 ± 12, 49 ± 16, and 50 ± 19 years, respectively, P  < 0.05 in each). Cox proportional hazard analysis revealed for the first time that, compared to mutation negatives, truncating mutation carriers had higher risk for lethal VAs, and especially for onset by their 40s, in an age‐dependent manner (RR = 4.6, P  < 0.01 by their 40s; RR = 2.9, P  = 0.01 by their 50s). Conclusion: The genetic background of Japanese ARVD/C probands is distinct from that of Caucasian probands, leading to distinct prognosis. The most affected gene mutations in Japanese probands were missense mutations in DSG2 leading to modest outcome, whereas PKP2 truncating mutations were the second most and might be a strong marker for lethal VAs in non‐Caucasian Japanese ARVD/C probands. Abstract : Japanese ARVD/C probands have unique genetic backgrounds that are predominated by DSG2 missense mutation followed by PKP2 truncating mutations. Truncating mutation carriers showed worse outcome in the age‐dependent manner than those with missense mutations or mutation negatives. Truncating mutation per se plays a critical role in predicting outcome.